GAMBARAN EFEK SEDASI KETAMIN PROPOFOL PADA PASIEN KURETASE DENGAN GENERAL ANESTESI BERDASARKAN BISPECTRAL INDEX SCORE - Amin Ghoni Ghofur; Amin Susanto; Prasanti Adriani (LPPM Universitas Harapan Bangsa, 2023)
Sedation is reduction of irritability or agitation by administration of sedative drugs. Sedation procedures are performed on patients who have anxiety and pain. Curettage is invasive procedures for women who require sedation procedures. Inadequate sedative during curettage can cause restlessness. Bad management of pain and anxiety should impact on women's psychological trauma. Ketamine-Propofol is a combination sedative drug that is effective, safe sedation and analgesia. This study aims to overview the sedative effects of ketamine propofol on curettage patients with general anesthesia based on the Bispectral index score at Margono Soekarjo Hospital, Purwokerto. The design of this study uses a descriptive observational. The sampling technique used in this research is random sampling with 38 respondents. The results showed that the sedation depth was good, the mean arterial pressure was optimal, the pulse rate was normal, the respiratory rate was normal, and the saturation was normal. Keywords: Sedation Depth, BIS, Curettage, Ketamine-Propofol